Mexican entrepreneurial responses to economic liberalisation: an exploratory study. (25th May 2005) - Leroy-Beltran, Catherine; Haar, Jerry; Beltran, Oscar A.
The exploratory study examines the responses of Mexican small and medium-sized enterprises (SME) to economic liberalisation. Two winning sectors for Mexico under NAFTA – apparel and plastics – and two losing sectors – textiles and printing/media – are analysed to determine the extent to which external factors and firm-level behaviour affect competitiveness. Findings reveal that regardless of the sector (winner or loser), macroeconomic policy choices, or NAFTA's provisions, it is the management of the firm (including vision, leadership, entrepreneurial attitude and behaviour, and decisions related to finance, marketing, production, and the deployment of human capital) that is by far the most important determinant of success.